Kepemimpinan Pesantren - Ahmadi Ahmadi (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2020)
This study examines the leadership of the Kiai at the Hidayatul Insan Islamic Boarding School, Fii Ta'Limiddin, Palangka Raya City with the formulation of the nature of pesantren leadership and how to integrate Islamic boarding school culture and Dayak culture in the Hidayataul Insan Islamic Boarding School, Palangka Raya City. The research was conducted using a phenomenological approach through interviews, observation, and documentation techniques. Data analysis was carried out through three activity streams. The results showed that the leadership of the pesantren is a leadership phenomenon that tends to be autocracy in which the highest power and authority is in the hands of the Kiai. Integrative leadership as a cooperative and democratic leadership model can be an alternative model of leadership, especially in the context of cultural integration in Islamic boarding schools